Motor Unit Discharge Rates During Maximal Fatiguing Eccentric Contractions and Recovery in the Human Elbow Extensors. - BASILE, DANIEL C.; RICE, CHARLES L. (Medicine & Science in Sports & Exercise, 2026)
Introduction: Eccentric (ECC) contractions are uniquely characterized by higher maximal torque output compared with concentric or isometric actions. However, this advantage is accompanied by greater and more prolonged torque loss following fatiguing ECC exercise compared with other modalities. Although muscle contractile responses to dynamic fatiguing contractions have been documented, the neural control of ECC contractions—particularly at the level of individual motor units—remains poorly understood. The purpose was to evaluate motor unit discharge rate (MUDR) modulation during and in recovery after a maximal effort ECC fatiguing task. Methods: Single motor unit activity was recorded with fine-wire electrodes inserted into the triceps brachii muscle. Participants completed an elbow extension protocol with subsequent recovery for 30 min, involving repetitive sets of 10 maximal repetitions until 50% torque loss relative to baseline maximal ECC torque. Results: MUDR declined substantially (>35%) from baseline to task failure (37.1 vs 23.1 Hz, P ≤ 0.001) and did not return to baseline values until 10 min of recovery (P = 0.597). However, both electrically stimulated twitch torque and maximal voluntary ECC torque remained depressed at 30 min (P = 0.001), relative to baseline. Conclusions: This study provides a novel characterization of motor unit behavior during fatigue induced by maximal ECC contractions, revealing a significant reduction consistent with prior evidence of impaired MUDR under other fatiguing tasks. In addition, results indicate that prolonged torque depression (30 min post-task failure) following the ECC fatiguing task is primarily attributable to peripheral muscle impairments, as MUDR recovered to baseline within ~10 min.